A Glimpse into the Future: Cross‐border Judicial Cooperation in Insolvency Cases in the European Union. Issue 2 (21st April 2015) - Wessels, Bob
Abstract After 2 years of study, discussion and consultation, in February 2015, the EU Cross‐Border Insolvency Court‐to‐Court Cooperation Principles were published. The EU Cross‐Border Insolvency Court‐to‐Court Cooperation Principles ('EU JudgeCo Principles') contain 26 principles. The EU JudgeCo Principles aim to strengthen efficient and effective communication between courts in EU Member States in insolvency cases with cross‐border effects. The EU JudgeCo Principles, in short, include principles on their non‐binding status and their objectives, case management of courts and the equal treatment of creditors, and principles about the judicial decisions itself, on the reasoning and for instance on providing a stay or moratorium. Several principles relate to the course of the proceedings, such as notifications and authentication of documents, and the last principles concern the outcome of judicial cooperation, for instance, cross‐border sales, assistance to a reorganisation or rules for binding creditors to an international reorganisation plan. The Principles include 18 EU Cross‐Border Insolvency Court‐to‐Court Communications Guidelines ('EU JudgeCo Guidelines'). These EU JudgeCo Guidelines aim to facilitate communications in practice, in individual cross‐border cases. The EU JudgeCo Principles try to overcome present obstacles for courts in EU Member States such as formalistic and detailed national procedural law, concerns about a judge's impartiality, uneasiness with the use of certain legal concepts and terms, and, evidently, language. Presently, court‐to‐court communication between judges in insolvency matters in the EU, especially on the continent, is limited to only a few cases. In the near future, judicial cooperation and communication will be a cornerstone in the efficient and effective administration of insolvency cases within the EU. The EU JudgeCo Principles will then certainly serve as a significant guide. Copyright © 2015 INSOL International and John Wiley & Sons, Ltd